PENGARUH BUDDHISME TERHADAP NEO-KONFUSIANISME DI CINA - Lasiyo Lasiyo (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2018)
This paper aims to examine the influence of Indian Buddhism toward Chinese Neo-Confucianism through philosophical perspective. This study uses library research; hermeneutical philosophical method which consists of three elements: descriptive, historical continuity and reflective. Based on data analysis, conclusion can be made such as: Firstly, the influence of Buddhism from India is acceptable and growth rapidly in China because people in China were unsatisfied toward Confucianism and Taoism. Secondly, Neo-Confusianism was a new development, borrowing much from Buddhim and Taoism, it appear as the reaction from the Confuciansim againts the development of Buddhism in China. Thirdly, the Confucianists realized that to compete with Buddhism, they have to give a philosophical thougths from the classics Chinese philosophy and adjust it to nowdays situation and people condition. Fourthly Neo-Confusianism’s thought emphasis on Metaphysics and Ethics in theoritically, therefore it have not fix the Economic and the prosperty in society. Fiftly, Neo-Confusianism reconstructed philosophical thought which the society believe and some from Buddhism